Model Fikir–Cakap–Tulis dalam Pembelajaran Menulis Cerita Pendek - Suryanti (Kodepena Indonesia, 2020)
Abstract This study aims to determine differences in short short writing skills that are significant between students who take part in learning using the Thinking - Proficient - Write model and students who take part in learning without using the Thinking-Write-Writing model, as well as testing the effectiveness of the written-thinking models in learning to write Short stories of class X students of SMA Negeri 4 Baubau City. This research is an experimental research with protest-posttest group design. The variables in this study are independent variables, namely Think-Talk-Write, and the dependent variable is short story writing skills. The population in this study were all grade X students of SMA Negeri 4 Baubau. The sample used in this study amounted to two classes, with the division of one class as a control class and one class as an experimental group. Samples were determined using cluster random sampling techniques. From the determination using cluster random sampling technique, it was obtained X-6 class as an experimental group, and X-9 class as a control class. Date collection techniques using the test, in the form of a short story writing test. Date analysis techniques were performed using pretest and posttest with t-test. The results of this study indicate that there are significant differences in short story writing skills between students who take part in learning by using written-thinking models and students who take lessons without using written-thinking models. This is evident from the t-test on the pretest and posttest scores of the experimental group resulting in a tcount of 13,356 with a df (degree of freedom) of 31 and a value of P = 0,000. In addition, the results of the t test showed that the effective writing-literacy model was used in learning to write short stories, because P ˂ 0.05 = significant. Keywords: Proficient-Write, short story writing skills.